Testing and Comparing Antifungal Medications to Natural Remedies - Kyna Bhandari, (International Journal of Scientific Research in Science and Technology, 2024)
This research paper aims to test and compare natural remedies to antifungal medications to see if they can be viable replacements for the medications. It aims to offer alternatives to people who may not have access to antifungal medications and avoid the overuse of medication. Through incubation, it found that garlic was an effective antifungal and the extent of its effect was the same as the antifungal medications, while castor oil and coconut oil were not as effective. Therefore, it states that garlic is a viable alternative to antifungal medications for yeast infections and encourages further testing to find more replacements for various types of infections.
Keywords: Antifungal Medications; Natural Remedies; Fucicort; Triben-XT